Sensitivity and Optimization Analysis of Torsional Behavior in Multicellular Thin-Walled Tubes - Alshannaq, Ammar A.; Tamimi, Mohammad F.; Abu Qamar, Muʹath I. (Salehan Institute of Higher Education, 2024)
Multicellular thin-walled tubes are widely used due to their lightweight, economical design, and superior shear and torsional performance. Their design is sometimes governed by the available materials and the required dimensions. The current study uses advanced sensitivity analysis with meta-modeling tools to understand how different geometric and mechanical factors affect the torsional performance of multicellular thin-walled tubes. The geometric factors include the length, thickness, and width of the beams, while the mechanical properties involve the shear modulus. Variance-based sensitivity analysis is used to assess how variations in these factors impact the rate of twist, torsional stiffness, and shear stress. The interconnected relations between input parameters are exploited for optimal design and superior performance. The results revealed that for a three-celled tube, thick horizontal interior elements with thin deep vertical elements and thin exterior elements provide an optimal design when the cross-sectional area is constrained. This finding, combined with varying the geometrical and material properties, results in an optimal design using CFRP composites when constrained by minimizing the total weight and superior torsional performance. The analysis can be extended to include other constraint(s), but changing the design constraints might change the optimal design. Doi: 10.28991/CEJ-2024-010-09-09 Full Text: PDF